PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DSLR CANON DI KOTA SEMARANG - Wicaksono, Alifian Rully; DS, Agus Hermani (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
The needs of today's society about documentation tools has become a ordinary needs and almost any people had use of photographic equipment such as cameras. As time goes by, types of camera is always evolving. Digital Single Lens Reflex or DSLR is one type of camera that can be used for people and especially photographers. Canon is one of the famous brand of digital SLR in the world. However, strict competition among providers of photographic products and the emergence of new types of cameras that can adjust the times and people's lifestyle, making the Canon DSLR product sales declined, particularly in the city of Semarang.The purpose of this research is to determine the effect of product quality and brand image on purchasing decisions of Canon DSLR in Semarang City. The type of research is explanatory research. The population in this research is the owner of a Canon DSLR in Semarang with the number of samples taken was 100 respondents. Sampling using purposive sampling technique. Measurement scale using Likert scale. The analytical method used is the correlation test, determination, simple linear regression, multiple linear regression, t-test and F-test using SPSS program version 18.Based on the results of the research, revealed that the partially, product quality and brand image has positive influence on the purchasing decision which is indicated by result of the value of t test bigger than t table. Significantly, variable product quality and brand image has positive influence towards purchasing decision indicated by value of F test larger than F table.And the advice that can be given is product quality improvement, especially in the DSLR’s ease of use, aesthetics improvements, and also provide easier access to consumers towards service center. Besides, Canon also need to make Canon's attributes more easily recognized by the public as well as applying the innovation of its products in order to not to bear the impression of monotonous and outdated tools.